PROCESS OPTIMISATION AND CHARACTERISATION OF FRAGRANCE SUITED MECHANICALLY EXPRESSED NIGERIAN LIME SEED OIL (Nigerian Journal of Technology, 2018)
This study determined the optimal process parameters for the extraction of Lime (Citrus aurantifolia) Seed Oil (LSO) for fragrance production. A Box Behnken Design (BBD) of Response Surface Methodology (RSM) was used to design the LSO extraction using hydraulic press. The effect of various combinations of temperature, heating time and pressing time on oil yield, specific gravity, acid value, saponification value, FFA, Iodine and peroxide values were investigated. The oil produced was analysed using Gas Chromatography – Mass Spectrophotometer (GC-MS). The R2 -values of models ranged between 0.998 and 0.999 and adjusted R2 between 0.994 and 0.998. A maximum of 29.21 % of LSO yield was obtained with specific gravity (0.861), acid value (2.86 mg KOH/g); saponification value (185.3 mg KOH/g), FFA (? 1.43 %), Iodine value (107.8 g I2/100 g) and peroxide value (15meq/kg) at the optimal process parameters of 83oC, 8 min and 7 min temperature heating and pressing time respectively. The physico-chemical analysis of the lime seed oil indicated that the oil could be used for fragrance.  http://dx.doi.org/10.4314/njt.v37i2.9